A Case Report of Well-Differentiated Liposarcoma Presenting as a Primary Inguinal Mass: Diagnostic Challenges and Management - Komang Budhi Pradnya Wibawa; Gede Bayu Wedanta Netra (International Medical Journal Corp. Ltd, 2025)
Introduction: Liposarcoma (LPS) is the most common soft tissue sarcoma in adults, yet its presentation as a primary mass in the inguinal region is exceedingly rare. This atypical location poses a significant diagnostic challenge, as the clinical signs often mimic more common benign conditions such as inguinal hernia or lipoma, which can lead to delayed diagnosis or inadequate initial management. This report details a case of well-differentiated liposarcoma (WDLS) in the inguinal canal, highlighting the clinical, radiological, and pathological nuances critical for accurate diagnosis and definitive treatment. Case Illustration: A 49-year-old male presented with a one-month history of a right inguinal lump that had rapidly enlarged over the preceding week, accompanied by intermittent pain. Physical examination revealed a mobile, tender mass measuring approximately 2x3 cm. Ultrasound imaging was pivotal, identifying a solid, heterogeneous, vascularized lesion, which raised the suspicion of a neoplasm beyond a simple lipoma. The patient subsequently underwent a wide excisional biopsy.Histopathological examination revealed a tumor composed of mature adipocytes with scattered atypical, hyperchromatic stromal cells and neoplastic lipoblasts, confirming the diagnosis of well-differentiated liposarcoma. A notable and potentially misleading feature was the presence of a prominent